Načrtovanje, demografija in Slovenija - Jakoš, Aleksander (Urbani izziv, 2009)
In this article, the issue of demographics is presented as one of the most important factors in regard to the future development of Slovenia. We are still not fully aware of the consequences of the demographic development in the past, which has caused the current situation. The balance between the active and retired population is disturbed, as the percentage of retired persons is on the increase. This process will continue, because the number of retirements will increase in the future, mainly due to the demographic reasons. In regard to the current age the structure of the population in Slovenia, we can expect a huge and absolute increase in the number of elderly people and an even faster increase in the percentage of elderly people in the entire population. The number of retired persons will indirectly increase due to the longer life expectancy. In a demographic sense, the increase of elderly people means a significantly higher annual number of deaths and therefore a strong negative natural growth. This will be even more evident due to the significant decrease of the number of births in the last 30 years. This problem arises not only from low birth rates, but also due to the fact that the generations of women in their fertility period are less numerous.
Keywords: demografija; demografski razvoj; demography; regionalno planiranje; Slovenia; Slovenija; starost